A UNIFIED DIGITAL ECOSYSTEM APPROACH TO ENTERPRISE MANAGEMENT AND DIGITAL SECURITY IN THE DIGITAL ECONOMY (World Economics and Finance Bulletin, 2025)
This article provides a scientific analysis of issues related to enterprisemanagement and digital security in the context of the digital economy, basedon information and communication technologies (ICT). Within the frameworkof the study, an approach aimed at organizing management processes, internaland external security, and operational monitoring through a unified digitalecosystem of enterprises is substantiated. This approach enables theintegration of managerial decision-making, risk identification and control, andbusiness process automation within a single digital environment. The articlescientifically demonstrates that the coordinated application of digitaltechnologies such as CRM, ERP, PLM, CALS, and SMART-ERP constitutes a keyfactor in improving enterprise management efficiency and strengtheningeconomic security. The research findings provide a methodological basis fordeveloping practical recommendations to enhance management activities andsecurity processes in enterprises through a digital ecosystem–based approach.
Keywords: unified digital ecosystem; digital economy; enterprise management; digital security